Conductive paste adaptive to back thin poly layer and preparation method and application thereof

By adding silver nanowires to the conductive paste, the contact area and reactivity of silver powder and glass powder are enhanced, and the problem of poor adaptability of the fine gate paste on the back of the TOPcon battery and the thin poly layer is solved, thereby improving the conductivity and solar cell efficiency.

CN119170323APending Publication Date: 2024-12-20NANTONG AISHENG NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411286865.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In the TOPcon battery of solar cells, the poor adaptability of the fine gate slurry on the back and the thin poly layer leads to poor conductivity and affects the battery performance and efficiency.

Method used

A conductive paste including 80 to 90 parts by mass of silver powder, 1.2 to 3.5 parts by mass of glass powder, 7 to 14 parts by mass of organic carrier, and 1 to 10 parts by mass of silver nanowires are used, and the silver nanowires are used as silver powder. The bridge between the glass powder enhances contact area and reactivity and improves conductivity.

Benefits of technology

The adaptability and conductivity of the conductive paste to the thin poly layer is improved, the contact resistance is reduced, and the photoelectric conversion efficiency of solar cells is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170323A_ABST
    Figure CN119170323A_ABST
Patent Text Reader

Abstract

The invention provides conductive paste adaptive to a back thin poly layer and a preparation method and application thereof, and belongs to the technical field of conductive paste. The conductive paste comprises the following components in parts by mass: 80-90 parts of silver powder; 1.2 to 3.5 parts by mass of glass powder; 7-14 parts by mass of an organic carrier; 1-10 parts by mass of an inorganic additive; wherein the inorganic additive is a silver nanowire. The inorganic additive component is added in the conductive paste, and the component adopts the silver nanowire which has a certain diameter and length and can be used as a bridge between silver powder, so that on one hand, the contact area of silver powder accumulation can be increased, contact with a poly layer can be formed, and silver powder sintering is promoted to be more compact; the silver nanowire is easier to react with the glass powder, so that the concentration of silver particles in the glass is increased, the contact resistance is reduced, the conductivity of the conductive paste is improved, and the problem of adaptability between the paste and a thin poly layer is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of conductive pastes, and in particular relates to a conductive paste for adapting to a thin poly layer on the back side, and a preparation method and application thereof. Background Art

[0002] Solar cells use the "photovoltaic effect" to achieve photoelectric conversion and have been commercialized. With the replacement of solar cells, the efficiency of photoelectric conversion has gradually increased. Conductive silver paste, as a key material for solar cell electrodes, has a direct impact on the performance of the cell. At present, the mainstream in the market is gradually transitioning from PERC cells to TOPcon cells. From a structural point of view, TOPcon cells have a thinner silicon oxide film on the back based on PERC cells. No laser grooving is required, which can further reduce surface recombination and make more effective use of carriers. During the sintering process, the fine grid slurry on the back needs to burn through the SiNx layer and contact the poly direct silicon layer. Therefore, for the fine grid slurry on the back of the TOPcon cell, the burn-through depth needs to be controlled during the sintering process, especially under the trend of thinning the poly layer. If the burn-through depth is too deep, it may cause poor compatibility between the conductive slurry and the poly layer, thereby affecting the performance and efficiency of the solar cell. Therefore, it is necessary to solve the problem of compatibility between the slurry and the thin poly layer.

[0003] The current conductive silver paste is mainly composed of three parts: organic carrier, silver powder and glass powder. Among them, glass powder, as the intermediate phase transition layer, is the main part for transmitting electrons. It determines whether the battery can form a good ohmic contact and indirectly affects the performance of the paste. However, since it only accounts for a small proportion, the paste still cannot meet the requirements of forming a good fit with the poly layer and has poor conductivity. Summary of the invention

[0004] The present disclosure aims to solve at least one of the technical problems existing in the prior art, and provides a conductive paste for adapting to a thin poly layer on the back side, and a preparation method and application thereof.

[0005] In one aspect of the present disclosure, a conductive paste for adapting a thin poly layer on the back side is provided, the conductive paste comprising:

[0006] 80-90 parts by weight of silver powder;

[0007] 1.2 to 3.5 parts by mass of glass powder;

[0008] 7 to 14 parts by weight of an organic carrier;

[0009] 1 to 10 parts by mass of inorganic additives; wherein,

[0010] The inorganic additive is silver nanowire.

[0011] Optionally, the silver nanowire has a diameter of 20 to 70 nm and a length of 5 to 20 μm.

[0012] Optionally, the silver nanowire has a diameter of 30 to 60 nm and a length of 5 to 10 μm.

[0013] Optionally, the organic carrier comprises:

[0014] 10 to 40 parts by mass of an organic resin;

[0015] 20 to 50 parts by mass of an organic solvent;

[0016] 1 to 30 parts by mass of additives.

[0017] Optionally, the organic resin is one or more of polybutadiene homopolymer, terminal hydroxyl polybutadiene modified resin, maleic anhydride polybutadiene modified resin, styrene-butadiene copolymer, acrylic resin, acrylate-maleic anhydride copolymer or styrene-maleic anhydride copolymer, and long-chain alkyl acrylate copolymer.

[0018] Optionally, the organic solvent is one or more of diethylene glycol butyl ether, polyoxymethylene dimethyl ether, butyl carbitol, dibutyl phthalate, and diethylene glycol butyl ether acetate.

[0019] Optionally, the additive is one or more of silicone oil, saturated polyol EO grafts and phosphate derivatives thereof, unsaturated polyol EO grafts and phosphate derivatives thereof.

[0020] The present disclosure provides a method for preparing the conductive paste for the back thin poly layer as described above, the method comprising:

[0021] Silver powder, glass powder, organic carrier and inorganic additive are mixed in a certain mass ratio, centrifuged and prepared into conductive slurry by a three-roll mill.

[0022] Optionally, the conductive paste has a viscosity of 20-200 Pa·s and a fineness of less than 5 μm.

[0023] Another aspect of the present disclosure provides an application of a conductive paste adapted for a thin poly layer on the back side, wherein the conductive paste described above is applied to a TOPcon battery.

[0024] The present disclosure proposes a conductive paste for adapting to the thin poly layer on the back side, and its preparation method and application. The conductive paste includes: 80-90 parts by mass of silver powder; 1.2-3.5 parts by mass of glass powder; 7-14 parts by mass of organic carrier; 1-10 parts by mass of inorganic additive; wherein the inorganic additive is silver nanowire. By adding an inorganic additive component to the conductive paste, and the component adopts silver nanowire, which has a certain diameter and length and can be used as a "bridge" between silver powders, on the one hand, it can enhance the contact area of ​​silver powder accumulation, form contact with the poly layer, and promote the sintering of silver powder to be more dense; on the other hand, the silver nanowire is more likely to react with the glass powder, so that the concentration of silver particles in the glass increases, the contact resistance is reduced, and the conductivity of the conductive paste is improved, solving the problem of the compatibility of the conductive paste with the thin poly layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM image of the gate lines formed by the conductive paste of Example 1 of the present disclosure;

[0026] Figure 2 This is a SEM image of a gate line formed by the conductive paste of Example 2 of the present disclosure;

[0027] Figure 3 This is a SEM image of the gate lines formed by the conductive paste of Comparative Example 1 of the present disclosure. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0029] In one aspect of the present disclosure, a conductive paste for adapting a thin poly layer on the back side is provided, the conductive paste comprising: 80 to 90 parts by mass of silver powder; 1.2 to 3.5 parts by mass of glass powder; 7 to 14 parts by mass of an organic carrier; 1 to 10 parts by mass of an inorganic additive; wherein the inorganic additive is silver nanowires.

[0030] In this embodiment, an inorganic additive component is added to the conductive paste, and the component adopts silver nanowires, which have a certain diameter and length and can serve as a "bridge" between silver powders. On the one hand, the contact area of ​​the silver powder accumulation can be enhanced to form contact with the poly layer, and the silver powder sintering can be promoted to be denser. On the other hand, the silver nanowires are more likely to react with the glass powder, so that the concentration of silver particles in the glass increases, the contact resistance is reduced, the conductivity of the conductive paste is improved, and the compatibility problem between the paste and the thin poly layer is solved.

[0031] It should be noted that the present embodiment does not impose any specific restrictions on the diameter and length of the silver nanowires, as long as they have a certain aspect ratio. At the same time, the content and specific substances of each component in the conductive paste are not specifically limited, as long as they are within the above range.

[0032] In some preferred embodiments, the diameter of the silver nanowire is 20-70 nm, and the length is 5-20 μm. For example, the diameter of the silver nanowire is 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, and the length of the silver nanowire is 5 μm, 7 μm, 10 μm, 12 μm, 13 μm, 15 μm, 18 μm, 20 μm, etc.

[0033] As a further preferred solution, the diameter of the silver nanowire can be preferably 30-60 nm, and the length is preferably 5-10 μm, for example, a silver nanowire with a diameter of 30 nm and a length of 5 μm, a silver nanowire with a diameter of 50 nm and a length of 5 μm, a silver nanowire with a diameter of 60 nm and a length of 5 μm, or a silver nanowire with a diameter of 30 nm and a length of 10 μm, a silver nanowire with a diameter of 40 nm and a length of 10 μm, a silver nanowire with a diameter of 60 nm and a length of 10 μm, etc. The silver nanowires with the above aspect ratios can serve as a "bridge" connecting the silver powders, forming good contact with the thin poly layer, and helping to improve the conductivity of the conductive paste. In particular, when the silver nanowires with a larger aspect ratio are preferred, it is more conducive to the occurrence of the reaction between the silver nanowires and the dissolved silver particles in the glass powder, thereby reducing the contact resistance. Of course, in other preferred embodiments, silver nanowires with other diameters and other lengths can also be selected.

[0034] In other preferred embodiments, the content of silver powder is preferably 80 parts by mass, 83 parts by mass, 85 parts by mass, 87 parts by mass, 90 parts by mass, etc. The silver powder can be spherical silver powder or flaky silver powder, etc. The spherical silver powder and flaky silver powder preferably have a particle size D50 < 2 μm and ablation < 0.8%.

[0035] In other preferred embodiments, the content of glass powder is preferably 1.2 parts by mass, 1.5 parts by mass, 2 parts by mass, 2.5 parts by mass, 3 parts by mass, 3.5 parts by mass, etc. The glass powder may preferably be a low-melting point glass powder, for example, a lead-boron system glass powder. The glass powder has a D50 particle size of <1um and is made by air flow milling and graded screening technology, and is a spherical powder.

[0036] As a further preferred embodiment, the glass powder includes 1% to 5% SiO2, 60% to 90% PbO, 1% to 5% TeO2, 1% to 10% ZnO, and 20% to 30% Bi2O3.

[0037] In some other preferred embodiments, the organic carrier comprises: 10 to 40 parts by mass of an organic resin, 20 to 50 parts by mass of an organic solvent, and 1 to 30 parts by mass of an additive.

[0038] As a further preferred embodiment, the organic resin is one or more of polybutadiene homopolymer, hydroxyl-terminated polybutadiene modified resin, maleic anhydride polybutadiene modified resin, styrene-butadiene copolymer, acrylic resin, acrylate-maleic anhydride copolymer or styrene-maleic anhydride copolymer, and long-chain alkyl acrylate copolymer. The content is preferably 10 parts by mass, 15 parts by mass, 20 parts by mass, 25 parts by mass, 30 parts by mass, 35 parts by mass, 40 parts by mass, etc.

[0039] As a further preferred embodiment, the organic solvent is one or more of diethylene glycol butyl ether, polyoxymethylene dimethyl ether, butyl carbitol, dibutyl phthalate, and diethylene glycol butyl ether acetate. The content thereof is preferably 20 parts by mass, 25 parts by mass, 30 parts by mass, 35 parts by mass, 40 parts by mass, 45 parts by mass, 50 parts by mass, etc.

[0040] As a further preferred embodiment, the additive is one or more of silicone oil, saturated polyol EO grafts and phosphated derivatives thereof, unsaturated polyol EO grafts and phosphated derivatives thereof. The content thereof is preferably 1 part by mass, 5 parts by mass, 10 parts by mass, 15 parts by mass, etc., 20 parts by mass, 25 parts by mass, 30 parts by mass, etc.

[0041] Another aspect of the present disclosure provides a method for preparing a conductive paste for a thin back poly layer, comprising: mixing silver powder, glass powder, an organic carrier, and an inorganic additive in a certain mass ratio, centrifuging the mixture, and preparing the conductive paste using a three-roll mill.

[0042] It should be noted that, during the preparation process, the contents of silver powder, glass powder, organic carrier, and inorganic additive can refer to the above text, for example, the silver powder content is 80-90 parts by mass, the glass powder content is 1.2-3.5 parts by mass, the organic carrier content is 7-14 parts by mass, the inorganic additive content is 1-10 parts by mass, and the inorganic additive is silver nanowires, and the total mass fraction of each component is 100 parts.

[0043] In some preferred embodiments, the conductive paste obtained in this embodiment has a viscosity of 20-200 Pa·s and a fineness of less than 5 μm.

[0044] The conductive paste of this embodiment forms contact with the thin poly layer, which helps to improve the conductivity of the conductive paste and solve the compatibility problem between the paste and the thin poly layer.

[0045] Another aspect of the present disclosure provides an application of a conductive paste adapted for a thin poly layer on the back side, that is, applying the conductive paste given above to a TOPcon battery.

[0046] In this embodiment, when the conductive paste given above is used as a back fine grid paste in a TOPcon cell, it helps to increase the aspect ratio of the grid line, reduce the contact resistance and line resistance of the cell, and thus improve the photoelectric conversion efficiency of the cell.

[0047] The conductive paste for adapting the back thin poly layer and its application will be further described below in conjunction with specific embodiments:

[0048] Example 1

[0049] The conductive paste of this example includes: 83.8 parts by mass of silver powder, 2.7 parts by mass of glass powder, 8.5 parts by mass of organic vehicle, and 5 parts by mass of inorganic additives.

[0050] Furthermore, the silver powder is spherical silver powder.

[0051] Furthermore, the glass powder adopts lead-boron system glass powder, and its formula is as follows: 5% SiO2, 60% PbO, 5% TeO2, 5% ZnO, and 25% Bi2O3.

[0052] Furthermore, the inorganic additive is silver nanowire, and the diameter of the silver nanowire is 60 nm and the length is 10 μm.

[0053] Furthermore, each mass part of the organic carrier includes 3.1 mass parts of an organic solvent (butyl diglycol, butyl carbitol = 2:1), 3.1 mass parts of an organic resin (acrylate-maleic anhydride copolymer, styrene-butadiene copolymer, long-chain alkyl acrylate copolymer = 1:1:1), and 2.3 mass parts of additives (silicone oil, saturated polyol EO grafted product: phosphated derivative of saturated polyol EO grafted product = 3:1:0.5).

[0054] Furthermore, the conductive paste of Example 1 is mixed and then centrifuged, and then a three-roll mill is used to prepare a conductive paste with uniform color.

[0055] Furthermore, the obtained conductive paste was used in TOPcon batteries to test the contact resistance, line resistance, line shape and other properties of the battery. The results are shown in Table 1. The contact resistance is 1.03Ω, the line resistance is 2.6374Ω, the line width is 34.67μm, the line height is 3.27μm, and the cross-sectional area is 131.56cm 2 .

[0056] Furthermore, the photoluminescence test of the battery was also performed. As shown in Table 2, the open circuit voltage was 0.73556 mV and the current density was 12.50 fA / cm 2 .

[0057] Furthermore, if Figure 1 As shown, in the gate line made of the conductive paste of this embodiment 1, there are fewer black voids in the cross section and the density is higher, which will increase the line resistance; and the junction between the gate line and the silicon wafer is relatively flat, and the area where the ohmic contact is formed is more uniform and stable, which helps to reduce the contact resistance.

[0058] Example 2

[0059] The conductive paste of this example includes: 83.8 parts by mass of silver powder, 2.7 parts by mass of glass powder, 8.5 parts by mass of organic vehicle, and 5 parts by mass of inorganic additives.

[0060] Furthermore, the silver powder is spherical silver powder.

[0061] Furthermore, the glass powder adopts lead-boron system glass powder, and its formula is as follows: 5% SiO2, 60% PbO, 5% TeO2, 5% ZnO, and 25% Bi2O3.

[0062] Furthermore, the inorganic additive is silver nanowire, and the diameter of the silver nanowire is 30 nm and the length is 10 μm.

[0063] Furthermore, each mass part of the organic carrier includes 3.1 mass parts of an organic solvent (butyl diglycol, butyl carbitol = 2:1), 3.1 mass parts of an organic resin (acrylate-maleic anhydride copolymer, styrene-butadiene copolymer, long-chain alkyl acrylate copolymer = 1:1:1), and 2.3 mass parts of additives (silicone oil, saturated polyol EO grafted product: phosphated derivative of saturated polyol EO grafted product = 3:1:0.5).

[0064] Furthermore, the conductive paste of Example 2 is mixed and then centrifuged, and then a three-roll mill is used to prepare a conductive paste with uniform color.

[0065] Furthermore, the obtained conductive paste was used in TOPcon batteries to test the contact resistance, line resistance, line shape and other properties of the battery. The results are shown in Table 1. The contact resistance is 0.57Ω, the line resistance is 2.3638Ω, the line width is 34.37μm, the line height is 3.30μm, and the cross-sectional area is 136.43cm 2 It can be seen that, compared with Example 1, the aspect ratio of the silver nanowires used in Example 2 is increased, and the specific surface area is larger, which is conducive to the reaction between the silver nanowires and the dissolved silver in the glass powder, thereby reducing the contact resistance.

[0066] Furthermore, the photoluminescence test of the battery was also performed. As shown in Table 2, the open circuit voltage was 0.73398 mV and the current density was 13.28 fA / cm 2 .

[0067] Furthermore, if Figure 2 As shown, in the gate line made of the conductive paste of Example 2, there are fewer black voids in the cross section and the density is higher, which will increase the line resistance; and the junction between the gate line and the silicon wafer is relatively flat, and the area where the ohmic contact is formed is more uniform and stable, which helps to reduce the contact resistance.

[0068] Comparative Example 1

[0069] The conductive paste of this example includes: 88 parts by mass of silver powder, 3 parts by mass of glass powder, and 9 parts by mass of organic vehicle.

[0070] Furthermore, the silver powder is spherical silver powder.

[0071] Furthermore, the glass powder adopts lead-boron system glass powder, and its formula is as follows: 5% SiO2, 60% PbO, 5% TeO2, 5% ZnO, and 25% Bi2O3.

[0072] Furthermore, each part by mass of the organic vehicle includes 3.3 parts by mass of an organic solvent, 3.3 parts by mass of an organic resin, and 2.4 parts by mass of an additive.

[0073] Furthermore, the conductive paste of Comparative Example 1 was mixed and then centrifuged, and then a three-roll mill was used to prepare a conductive paste with uniform color.

[0074] Furthermore, the obtained conductive paste was used in TOPcon batteries to test the contact resistance, line resistance, line shape and other properties of the battery. The results are shown in Table 1. The contact resistance is 1.26Ω, the line resistance is 2.9826Ω, the line width is 30.83μm, the line height is 6.95μm, and the cross-sectional area is 141.66cm 2 .

[0075] Furthermore, the photoluminescence test of the battery was also performed. As shown in Table 2, the open circuit voltage was 0.71433 mV and the current density was 26.35 fA / cm 2 .

[0076] Furthermore, if Figure 3 As shown, in the gate line made from the conductive paste of Comparative Example 1, there are more black voids in the cross section and the density is lower; and the junction between the gate line and the silicon wafer is uneven and has gaps.

[0077] Table 1 Contact resistance, line resistance and line type test results

[0078]

[0079]

[0080] Table 2 Test results of open circuit voltage and current density

[0081] Voc(mV) <![CDATA[JO(fA / cm 2 )]]> Example 1 0.73556 12.50 Example 2 0.73398 13.28 Comparative Example 1 0.71433 26.35

[0082] In summary, according to the gate line SEM results of Examples 1 and 2 and the comparative example, it can be seen that the inorganic additive has a relatively obvious effect on the line shape of the conductive paste. Compared with Comparative Example 1, the density of the gate lines of Examples 1 and 2 is improved, and there are fewer black voids in the cross section, which will reduce the line resistance; and the junction between the gate line and the silicon wafer is relatively flat, the area forming the ohmic contact is more uniform and stable, and the contact resistance is reduced. Corresponding to the test results in Table 1, it can be inferred that the inorganic additive plays a positive role in the conductive paste. Secondly, compared with the comparative example, in Examples 1 and 2, the JO of the conductive paste added with silver nanowires is small. The smaller the JO, the lower the metal composite, and the better the conductive performance of the paste.

[0083] The present disclosure proposes a conductive paste for adapting to a thin poly layer on the back side, and a preparation method and application thereof, which have the following beneficial effects compared to the prior art: by adding an inorganic additive to the conductive paste, the conductive paste is brought into contact with the poly layer, thereby improving the conductivity of the paste and solving the compatibility problem between the conductive paste and the thin poly layer.

[0084] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.

Claims

1. A conductive paste suitable for the thin poly layer on the back side, It is characterized in that The conductive paste comprises: 80-90 parts by weight of silver powder; 1.2 to 3.5 parts by mass of glass powder; 7 to 14 parts by weight of an organic carrier; 1 to 10 parts by mass of inorganic additives; wherein, The inorganic additive is silver nanowire.

2. The conductive paste for the thin poly layer on the back side according to claim 1, It is characterized in that The diameter of the silver nanowire is 20-70 nm, and the length is 5-20 μm.

3. The conductive paste for the thin poly layer on the back side according to claim 2, It is characterized in that The diameter of the silver nanowire is 30-60 nm, and the length is 5-10 μm.

4. The conductive paste for the back thin poly layer according to any one of claims 1 to 3, It is characterized in that The organic carrier comprises: 10 to 40 parts by mass of an organic resin; 20 to 50 parts by mass of an organic solvent; 1 to 30 parts by mass of additives.

5. The conductive paste for the back thin poly layer according to claim 4, It is characterized in that The organic resin is one or more of polybutadiene homopolymer, terminal hydroxyl polybutadiene modified resin, maleic anhydride polybutadiene modified resin, styrene-butadiene copolymer, acrylic resin, acrylate-maleic anhydride copolymer or styrene-maleic anhydride copolymer, and long-chain alkyl acrylate copolymer.

6. The conductive paste for the thin poly layer on the back side according to claim 4, It is characterized in that The organic solvent is one or more of diethylene glycol butyl ether, polyoxymethylene dimethyl ether, butyl carbitol, dibutyl phthalate, and diethylene glycol butyl ether acetate.

7. The conductive paste for the back thin poly layer according to claim 4, It is characterized in that The additive is one or more of silicone oil, saturated polyol EO grafts and phosphate derivatives thereof, unsaturated polyol EO grafts and phosphate derivatives thereof.

8. A method for preparing the conductive paste for the back thin poly layer as claimed in any one of claims 1 to 7, It is characterized in that The method comprises: Silver powder, glass powder, organic carrier and inorganic additive are mixed in a certain mass ratio, centrifuged and prepared into conductive slurry by a three-roll mill.

9. The method according to claim 8, It is characterized in that The conductive paste has a viscosity of 20-200 Pa·s and a fineness of less than 5 μm.

10. An application of conductive paste for thin poly layer on the back side, It is characterized in that The conductive paste described in claim 8 or 9 is applied to a TOPcon battery.

Citation Information

Cited By

  • Conductive slurry for xBC battery, preparation method, electrode and battery

    CN119943472A